Wpływ akcesji do Unii Europejskiej na poziom i relacje cenowe w rolnictwie polskim (analiza długookresowa) - Kiryluk-Dryjska, Ewa; Baer-Nawrocka, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The paper aims to present the impact of Polish accession to the EU on prices and price relations of agricultural products in Poland. The results show that after the accession the price volatility decreased. Lower values of price volatility indexes in Poland after the accession tend to decrease the price risk of production decisions.